Settlement of Infidelity Cases According to Customary Law in Lolotuara Village, Pulau Lakor District, Southwest Maluku Regency - Wessy, Yeheskel; Noya, Stelvia W. (Gayaku Publisher, 2023)
Settlement of Infidelity Cases According to Customary Law in Lolotuara Village, Pulau Lakor District, Southwest Maluku Regency. The problem in this legal research is how to resolve cases of infidelity. In accordance with the problem formulation in this legal research, the problems found in the indigenous community in Lolotuara are cases of infidelity which occur either between husband and wife of another person or between a husband or wife and another man or woman outside of the husband and wife relationship. . That if the case of infidelity occurs, there are also customary fines that can be implemented by Saniri Negeri Lolotuara as a customary institution that upholds customary values ​​that have been violated by individuals in society. This research is a normative juridical research, a problem solving approach through a conceptual approach, a statutory approach and a case approach, then from the results of the description conclusions and suggestions can be drawn. The results of the research show that the resolution of cases of infidelity through customary criminal sanctions in Lolotuara Village is carried out by requesting responsibility for men to marry girls. If the woman is the wife of the person who committed the affair then a customary fine is implemented, if they do not comply with the request to marry the girl then it is implemented. customary fines, if you are someone's wife then you are obliged to fulfill customary obligations, namely customary fines to the girl and the wife or husband of the person who has been harmed by the actions carried out by the parties. The mechanism for resolving and administering customary sanctions in Lolotuara can be accepted and implemented by customary sanctions because it is adhered to by the Lolotuara indigenous community and its existence is recognized in the national legal system. Due to this, the implementation of customary fines as a form of fulfilling customary obligations by the parties in cases of infidelity or adultery is still enforced in society because it has coercive power which is implemented by the Saniri of Lolotuara State, these customary sanctions are seen as fulfilling a sense of justice for Indigenous Peoples Lolotuara.